2022
DOI: 10.1111/apel.12352
|View full text |Cite
|
Sign up to set email alerts
|

The two faces of urbanisation and productivity: Enhance or inhibit? New evidence from Chinese firm‐level data

Abstract: This study employs industrial survey data from China's National Bureau of Statistics covering Chinese manufacturing enterprises during the period 1998–2007 to examine the impact of urbanisation on total factor productivity (TFP) in various industries. In recent years, urbanisation development has varied greatly across China. So Chinese cities can be divided into three urbanisation categories based on the proportion of the urban population to the total population: highly urbanised areas (60 per cent and over), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…1 We will then refer to the two types of productivity as OP (Olley-Pakes) and LP (Levinsohn-Petrin) productivity respectively, depending on the estimation method. Both Olley-Pakes and Levinsohn-Petrin methods have long been adopted, even recently, to measure microlevel productivity (Howell, 2016;Kuosmanen and Kuosmanen, 2021;Wang et al, 2022;Wu et al, 2022;Huang and Du, 2023) and confirmed with their validity.…”
Section: Productivitymentioning
confidence: 81%
“…1 We will then refer to the two types of productivity as OP (Olley-Pakes) and LP (Levinsohn-Petrin) productivity respectively, depending on the estimation method. Both Olley-Pakes and Levinsohn-Petrin methods have long been adopted, even recently, to measure microlevel productivity (Howell, 2016;Kuosmanen and Kuosmanen, 2021;Wang et al, 2022;Wu et al, 2022;Huang and Du, 2023) and confirmed with their validity.…”
Section: Productivitymentioning
confidence: 81%